Catalyst for acrylonitrile absorption tower tail gas treatment and preparation method and application thereof

By using metal skeleton support, active components and hydrothermal stabilized materials in the catalyst, a high activity and stability catalyst is prepared, which solves the problems of poor hydrothermal stability and poor removal effect of the catalyst in the prior art, and realizes the Effective treatment of the exhaust gas of the acrylonitrile absorption tower.

CN119303590AActive Publication Date: 2025-01-14PETROCHINA CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202310869630.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-14
Publication Date
2025-01-14
Estimated Expiration
2043-07-14

AI Technical Summary

Technical Problem

The catalysts used in the prior art for the exhaust gas treatment of acrylonitrile absorption towers have problems such as poor hydrothermal stability, low activity, and poor removal of methane and acrylonitrile unless the total methane hydrocarbons and acrylonitrile are not effective.

Method used

80-97 parts by mass of metal frame carrier, 0.5-1 parts by mass of active components, 5-10 parts by mass of additives, and 0.2-0.5 parts by mass of hydrothermal stabilized materials, specifically including platinum oxide and palladium oxide , titanium oxide, etc. are applied to the metal frame support by deposition complex impregnation method to prepare a catalyst with high activity and stability.

Benefits of technology

It significantly improves the hydrothermal stability of the catalyst and has excellent activity. It has good removal effect on the total non-methane hydrocarbons and acrylonitrile in the exhaust gas of the acrylonitrile device absorption tower. The exhaust gas index after treatment meets the national emission standards, and the catalyst coating is Firm bond, uniform coating, low shedding rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119303590A_ABST
    Figure CN119303590A_ABST
Patent Text Reader

Abstract

The invention provides a catalyst for acrylonitrile absorption tower tail gas treatment as well as a preparation method and application thereof. The catalyst comprises 80-97 parts by mass of a metal framework carrier, 0.5-1 part by mass of an active component, 5-10 parts by mass of an auxiliary agent and 0.2-0.5 part by mass of a hydrothermal stable material, wherein the active component is at least one of platinum oxide and palladium oxide; the auxiliary agent is at least one of a titanium oxide, a vanadium oxide, a chromium oxide, a manganese oxide, a cobalt oxide, a nickel oxide, a copper oxide and a rare earth metal oxide; the hydrothermal stable material is magnesium aluminate spinel. The catalyst provided by the invention has excellent activity and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of gas purification, and in particular relates to a catalyst for treating tail gas from an acrylonitrile absorption tower, and a preparation method and application thereof. Background Art

[0002] The acrylonitrile production process adopts propylene ammoxidation technology, with propylene and ammonia as the main raw materials. Under the action of catalyst, acrylonitrile and other by-products are generated by reaction, and then acrylonitrile products are obtained through rapid cooling, recovery, refining and other process flows. The waste gas discharged from the top of the absorption tower during normal production of the acrylonitrile device is called the absorption tower tail gas. In addition to nitrogen, carbon dioxide, and water vapor, it also contains a certain amount of propane, propylene, acrylonitrile, etc. Direct discharge into the atmosphere will cause pollution to the environment. The pollutants in the absorption tower tail gas need to be purified to achieve non-methane total hydrocarbons ≤ 120mg / m 3 , acrylonitrile content ≤ 0.5mg / m 3 national emission requirements.

[0003] At present, the main methods for treating tail gas include thermal combustion and catalytic oxidation. The thermal combustion method heats harmful gases to 600-800℃, converts various organic substances in the tail gas into inorganic substances such as carbon dioxide and water, and discharges them into the atmosphere together. The concentration of nitrogen oxides in the flue gas can be controlled by controlling the combustion temperature and the excess air to meet the emission standards. This treatment method has a large amount of flue gas emissions and contains pollutants such as nitrogen oxides. It also consumes a lot of fuel, is not conducive to energy saving, and the overall treatment cost is relatively high. The catalytic oxidation method is to completely oxidize and decompose the combustibles in the harmful gas at 350-600℃ under the action of a catalyst. Generally, no auxiliary fuel is required. It can be used for the purification of low-concentration, complex-component combustibles. This method has high purification efficiency, low reaction temperature, and does not produce secondary pollution.

[0004] Catalytic oxidation catalysts mainly include precious metal catalysts and non-precious metal oxide catalysts. Precious metal catalysts have excellent catalytic oxidation activity, but low thermal stability, easy to sinter and lose at high temperature; non-precious metal oxide catalysts such as copper, cobalt, manganese and chromium oxides and composite oxides have high thermal stability, but their catalytic oxidation activity is lower than that of precious metals.

[0005] CN101362051A discloses a novel process for treating acrylonitrile tail gas, which has the dual functions of catalytic oxidation and catalytic reduction. However, the process uses traditional noble metal oxidation catalysts and vanadium / titanium / tungsten reduction catalysts. Such catalyst materials have the disadvantages of high cost and relatively low SCR catalytic removal performance.

[0006] CN 102513145A discloses an Fe molecular sieve SCR catalyst for purifying NOx in acrylonitrile oxidation tail gas and a preparation method thereof, wherein a commercial ZSM-5 molecular sieve, a Y-type molecular sieve, a ferrierite or a beta molecular sieve is used as a carrier, and an Fe zeolite with a mass fraction of 0.3-10.0% is introduced by an impregnation method or an ion exchange method. 3+ It is an active component to achieve efficient catalytic removal of NOx in the tail gas after acrylonitrile oxidation under oxygen-rich conditions.

[0007] CN102734812A discloses a method for removing cyanide-containing waste gas, which uses a transition metal-supported mesoporous molecular sieve catalyst to perform a catalytic reaction to remove cyanide-containing waste gas. The mesoporous molecular sieve carrier is: MCM-41, MCM-48, SBA-15, SBA-16, KIT-5 or KIT-6, the transition metal active component is: one or more of Cu, Co, Cr, Mn, Ag or V, the mass ratio of the carrier to the transition metal component is 1:0.02-0.07, the molecular sieve catalyst is placed in a fixed bed quartz reactor, the reactor temperature is raised to 350°C-650°C under normal pressure, and the mixed gas of cyanide-containing waste gas, oxygen and nitrogen is heated at a space velocity of 17000-24000h / min. -1 The waste gas is passed into the reaction furnace and removed through catalytic combustion. The waste gas removal efficiency of this method is low.

[0008] CN101362051A discloses a tail gas treatment process for an acrylonitrile device, which is suitable for the acrylonitrile waste gas discharged from the acrylonitrile device. The acrylonitrile tail gas is separated from free water by a gas-liquid separator and mixed with air. A noble metal honeycomb catalyst is used as a catalyst to perform a catalytic oxidation reaction to convert harmful volatile organic matter into carbon dioxide and water. A selective honeycomb catalyst is then used as a catalyst to perform a selective catalytic reduction reaction with added ammonia to reduce nitrogen oxides in the tail gas into nitrogen and water. The method is complex to operate, requires the addition of ammonia, and has high material consumption.

[0009] Therefore, the art still needs to further study the catalyst used for treating tail gas from an acrylonitrile absorber. Summary of the invention

[0010] The main purpose of the present invention is to provide a catalyst for treating tail gas from an acrylonitrile absorber, and a preparation method and application thereof, so as to overcome the defects of the catalyst in the prior art, such as poor hydrothermal stability, low activity, and poor effect of removing non-methane total hydrocarbons and acrylonitrile in tail gas.

[0011] In order to achieve the above object, the present invention provides a catalyst for treating tail gas from an acrylonitrile absorber, comprising 80-97 parts by mass of a metal skeleton carrier, 0.5-1 parts by mass of an active component, 5-10 parts by mass of an auxiliary agent, and 0.2-0.5 parts by mass of a hydrothermal stable material;

[0012] Among them, the active component is at least one of platinum oxide and palladium oxide; the auxiliary agent is at least one of titanium oxide, vanadium oxide, chromium oxide, manganese oxide, cobalt oxide, nickel oxide, copper oxide, and rare earth metal oxide; and the hydrothermal stable material is magnesium aluminum spinel.

[0013] The catalyst for treating tail gas from an acrylonitrile absorption tower of the present invention comprises: the metal skeleton carrier being an Al2O3 / Fe2O3 composite carrier.

[0014] The catalyst for treating tail gas from an acrylonitrile absorber of the present invention, wherein the active component is at least one of PtO2 and PdO2.

[0015] The catalyst for treating tail gas from an acrylonitrile absorber of the present invention, wherein the auxiliary agent is at least one of TiO2, V2O3, CrO2, MnO2, CoO, NiO, CuO, La2O3, CeO2, and IrO2.

[0016] In order to achieve the above object, the present invention also provides a method for preparing the above-mentioned catalyst for treating tail gas from an acrylonitrile absorber, comprising: mixing active components, additives, hydrothermal stable materials and water into a suspension, grinding the suspension, then coating the slurry on a metal skeleton carrier, drying, and calcining to obtain the catalyst for treating tail gas from an acrylonitrile absorber.

[0017] The preparation method of the catalyst for treating tail gas from an acrylonitrile absorption tower of the present invention comprises the steps of mixing active components, auxiliary agents, hydrothermal stable materials and water into a suspension, mixing auxiliary agents and water into a suspension, and then adding active components and hydrothermal stable materials.

[0018] The method for preparing a catalyst for treating tail gas from an acrylonitrile absorber of the present invention comprises the following steps: placing the carrier in a vacuum environment, and applying the prepared slurry to the metal skeleton carrier by deposition complexation impregnation at 150-180°C.

[0019] In order to achieve the above object, the present invention further provides the use of the above catalyst in removing non-methane total hydrocarbons and acrylonitrile from tail gas of an acrylonitrile absorption tower.

[0020] The application of the present invention, wherein the reaction conditions for removing non-methane total hydrocarbons and acrylonitrile from the tail gas of the acrylonitrile absorber are: reaction temperature 240-650°C, reaction pressure 0.01-0.015MPa, reaction space velocity 10000-15000h -1 The volume ratio of tail gas from the acrylonitrile absorption tower to air is 2.5-3.5.

[0021] Beneficial effects of the present invention:

[0022] The invention greatly improves the hydrothermal stability of the catalyst by adding magnesium aluminum spinel; at the same time, the catalyst of the invention has excellent activity and has good removal ability for non-methane total hydrocarbons and residual acrylonitrile in the tail gas of the acrylonitrile absorption tower; in addition, the catalyst of the invention has the characteristics of high activity and strong stability, and the tail gas index after treatment meets the emission standards required by the state.

[0023] The catalyst coating prepared by the method of the invention has firm bonding, uniform coating and low coating shedding rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The results are shown in Figure 1 for evaluating the catalyst of the present invention after 1000 h of catalysis. DETAILED DESCRIPTION

[0025] The technical scheme of the present invention is described in detail below. The following implementation modes are implemented on the premise of the technical scheme of the present invention, and a detailed implementation process is given. However, the protection scope of the present invention is not limited to the following implementation modes. The structures or experimental methods of specific conditions are not specified in the following implementation modes, and generally conventional conditions are followed.

[0026] The present invention provides a catalyst for treating tail gas from an acrylonitrile absorption tower, comprising 80-97 parts by mass of a metal skeleton carrier, 0.5-1 parts by mass of an active component, 5-10 parts by mass of an auxiliary agent, and 0.2-0.5 parts by mass of a hydrothermal stable material;

[0027] Among them, the active component is at least one of platinum oxide and palladium oxide; the auxiliary agent is at least one of titanium oxide, vanadium oxide, chromium oxide, manganese oxide, cobalt oxide, nickel oxide, copper oxide, and rare earth metal oxide; and the hydrothermal stable material is magnesium aluminum spinel.

[0028] The catalyst of the present invention has good hydrothermal stability due to the addition of the hydrothermal stable material magnesium aluminum spinel. In addition, the catalyst of the present invention uses a metal skeleton as a carrier, platinum and palladium as active components, and titanium, vanadium, chromium, manganese, cobalt, nickel, copper, rare earth metals, etc. as auxiliary agents, has excellent activity, and has good removal ability for non-methane total hydrocarbons and residual acrylonitrile in the tail gas of the acrylonitrile device absorption tower; furthermore, the catalyst of the present invention has the characteristics of high activity and strong stability, and the tail gas index after treatment meets the emission standards required by the state.

[0029] In one embodiment, the metal skeleton carrier of the present invention is an Al2O3 / Fe2O3 composite carrier. In another embodiment, the metal skeleton carrier is in a shaped solid plate state, and the solid plate is composed of Al2O3 and Fe2O3. The catalyst of the present invention includes 80-97 parts by mass of the metal skeleton carrier, in one embodiment, for example 85-97 parts by mass, 88-95 parts by mass.

[0030] The active component of the catalyst of the present invention is at least one of platinum oxide and palladium oxide; in one embodiment, the active component of the catalyst of the present invention is at least one of PtO2 and PdO2. The catalyst of the present invention includes 0.5-1 parts by mass of the active component, and in one embodiment, for example, 0.6 parts by mass, 0.7 parts by mass, 0.8 parts by mass, or 0.9 parts by mass.

[0031] The promoter of the catalyst of the present invention is at least one of titanium oxide, vanadium oxide, chromium oxide, manganese oxide, cobalt oxide, nickel oxide, copper oxide, and rare earth metal oxide. In one embodiment, the promoter of the catalyst of the present invention is at least one of TiO2, V2O3, CrO2, MnO2, CoO, NiO, CuO, La2O3, CeO2, and IrO2.

[0032] The catalyst of the present invention comprises 5-10 parts by mass of an auxiliary agent. In a specific embodiment, the catalyst of the present invention comprises 6 parts by mass, 7 parts by mass, 8 parts by mass, or 9 parts by mass of an auxiliary agent.

[0033] In a specific embodiment, the catalyst of the present invention is composed of 88.8 parts by mass of a metal skeleton carrier, 1.0 parts by mass of CoO, 1.0 parts by mass of NiO, 1.0 parts by mass of TiO2, 1.0 parts by mass of CrO2, 1.0 parts by mass of MnO2, 1.0 parts by mass of CuO, 1.0 parts by mass of V2O3, 1.0 parts by mass of La2O3, 1.0 parts by mass of CeO2, 1.0 parts by mass of IrO2, 0.2 parts by mass of PtO2, 0.6 parts by mass of PdO2, and 0.4 parts by mass of magnesium aluminum spinel.

[0034] The hydrothermally stable material of the present invention is an inorganic composite material, preferably magnesium aluminum spinel. The catalyst of the present invention comprises 0.2-0.5 parts by mass of the hydrothermally stable material, for example 0.2 parts by mass, 0.3 parts by mass, 0.4 parts by mass, 0.5 parts by mass.

[0035] In one embodiment, the magnesium-aluminum spinel of the present invention is prepared by co-precipitation of magnesium salt and aluminum salt through a microreactor.

[0036] The present invention also provides a method for preparing the above-mentioned catalyst for treating tail gas from an acrylonitrile absorber, comprising: mixing active components, additives, hydrothermal stable materials and water into a suspension, grinding the suspension, then coating the slurry on a metal skeleton carrier, drying, and calcining to obtain the catalyst for treating tail gas from an acrylonitrile absorber.

[0037] In one embodiment, the present invention first mixes the auxiliary agent and water into a suspension, and then adds the active component and the hydrothermal stable material. In another embodiment, the method of applying the slurry to the metal skeleton carrier of the present invention is: the metal skeleton carrier is placed in a vacuum environment, and the prepared slurry is applied to the metal skeleton carrier by deposition complexation impregnation at 150-180°C.

[0038] In one embodiment, the present invention uses a ball mill to grind the suspension, and the particle size after grinding is 20-100 μm.

[0039] In one embodiment, after the slurry is coated on the metal skeleton carrier, the drying temperature is 100-120° C. The present invention does not specifically limit the calcination temperature, and the conventional calcination temperature in the art can be used.

[0040] The catalyst coating prepared by the method of the invention has firm bonding, uniform coating and low coating shedding rate.

[0041] The catalyst of the present invention can be used to remove non-methane total hydrocarbons and acrylonitrile in the tail gas of an acrylonitrile absorber in an industrial device. The tail gas is detected by gas chromatography after passing through a fixed bed reactor, and the catalyst activity is determined by the tail gas content. The reaction temperature of the catalyst of the present invention for treating the tail gas of the acrylonitrile absorber is 240-650°C, the reaction pressure is 0.01-0.015MPa, and the reaction space velocity is 10000-15000h -1 , the volume ratio of acrylonitrile absorption tower exhaust gas to air is 2.5-3.5.

[0042] In one embodiment, the non-methane total hydrocarbon content in the tail gas of the acrylonitrile absorption tower of the industrial device of the present invention is 16673 mg / m 3 , acrylonitrile is 40mg / m 3 .

[0043] The technical solution of the present invention will be further described in detail below through specific embodiments. Unless otherwise specified, the "parts" referred to below refer to parts by mass.

[0044] Sources of raw materials or equipment: Acrylonitrile tail gas, Daqing Petrochemical Company; Gas chromatography, Tianmei.

[0045] Evaluation and analysis method: self-built

[0046] Example 1

[0047] 1.0 part of TiO2, 1.0 part of CrO2, 1.0 part of CuO, 1.0 part of V2O3, 1.0 part of La2O3 and 100 parts of deionized water were mixed into a uniform suspension, and 0.5 parts of PtO2, 0.5 parts of PdO2 and 0.2 parts of magnesium aluminum spinel were added. The liquid was ground into a 20-100 μm slurry by a high-energy ball mill, and then the carrier was coated by deposition complex impregnation using quantitative vacuum coating technology, dried and calcined to make an integral catalyst CAT-1.

[0048] The prepared catalyst is calculated based on 100 parts by mass, minus the parts of the above-mentioned active components, additives, and hydrothermal stabilizing materials, and the remainder is the mass fraction of the carrier, which is the same as in the following embodiments.

[0049] Example 2

[0050] 2.5 parts of TiO2, 2.5 parts of CrO2 and 75 parts of deionized water were prepared into a uniform suspension, and 0.3 parts of PtO2, 0.3 parts of PdO2 and 0.3 parts of magnesium aluminum spinel were added. The liquid was ground into a 20-100 μm slurry by a high-energy ball mill. Then, the carrier was coated by deposition complex impregnation using quantitative vacuum coating technology, and then dried and calcined to make an integral catalyst CAT-2.

[0051] Example 3

[0052] 3.0 parts of TiO2, 1.0 parts of La2O3, 1.0 parts of CeO2 and 100 parts of deionized water were prepared into a uniform suspension, and 0.2 parts of PtO2, 0.3 parts of PdO2 and 0.4 parts of magnesium aluminum spinel were added. The liquid was ground into a 20-100 μm slurry by a high-energy ball mill. Then, the carrier was coated by deposition complex impregnation using quantitative vacuum coating technology, and then dried and calcined to make an integral catalyst CAT-3.

[0053] Example 4

[0054] 3.0 parts of CrO2, 2.0 parts of CuO and 100 parts of deionized water were prepared into a uniform suspension, and 0.4 parts of PtO2, 0.3 parts of PdO2 and 0.3 parts of magnesium aluminum spinel were added. The liquid was ground into a 20-100 μm slurry by a high-energy ball mill. The carrier was coated by deposition complex impregnation using quantitative vacuum coating technology, and then dried and calcined to make an integral catalyst CAT-4.

[0055] Example 5

[0056] 1.5 parts of TiO2, 1.5 parts of CrO2, 2.0 parts of MnO2, 1.0 parts of CuO, 1.0 parts of CeO2 and 210 parts of deionized water are prepared into a uniform suspension, and 0.5 parts of PtO2, 0.5 parts of PdO2 and 0.4 parts of magnesium aluminum spinel are added. The liquid is ground into a 20-100 μm slurry by a high-energy ball mill, and then the carrier is coated by deposition complex impregnation using quantitative vacuum coating technology, and then dried and calcined to make an integral catalyst CAT-5.

[0057] Example 6

[0058] 2.0 parts of TiO2, 2.0 parts of MnO2, 2.0 parts of V2O3, 2.0 parts of CeO2 and 160 parts of deionized water were mixed into a uniform suspension, and 0.2 parts of PtO2, 0.6 parts of PdO2 and 0.3 parts of magnesium aluminum spinel were added. The liquid was ground into a 20-100μm slurry by a high-energy ball mill, and then the carrier was coated by deposition complex impregnation using quantitative vacuum coating technology, dried and calcined to make an integral catalyst CAT-6.

[0059] Example 7

[0060] 3.0 parts of CoO, 1.0 parts of TiO2, 3.0 parts of La2O3, 1.0 parts of CeO2 and 100 parts of deionized water were prepared into a uniform suspension, and 0.4 parts of PtO2, 0.4 parts of PdO2 and 0.4 parts of magnesium aluminum spinel were added. The liquid was ground into a 20-100 μm slurry by a high-energy ball mill, and then the carrier was coated by deposition complex impregnation using quantitative vacuum coating technology, dried and calcined to make an integral catalyst CAT-7.

[0061] Example 8

[0062] 1.0 part of CoO, 1.0 part of NiO, 1.0 part of TiO2, 1.0 part of CrO2, 1.0 part of MnO2, 1.0 part of CuO, 1.0 part of V2O3, 1.0 part of La2O3, 1.0 part of CeO2, 1.0 part of IrO2 and 250 parts of deionized water were prepared into a uniform suspension, 0.2 part of PtO2, 0.6 part of PdO2 and 0.4 part of magnesium aluminum spinel were added, the liquid was ground into 20-100μm slurry by high-energy ball mill, and then the carrier was coated by deposition complex impregnation using quantitative vacuum coating technology, dried and calcined to make the integral catalyst CAT-8.

[0063] Example 9

[0064] 2.0 parts of CoO, 2.0 parts of CrO2, 2.0 parts of MnO2, 2.0 parts of CuO, 2.0 parts of La2O3 and 200 parts of deionized water are prepared into a uniform suspension, and 0.4 parts of PtO2, 0.6 parts of PdO2 and 0.5 parts of magnesium aluminum spinel are added. The liquid is ground into a 20-100μm slurry by a high-energy ball mill, and then the carrier is coated by deposition complex impregnation using quantitative vacuum coating technology, dried and calcined to make an integral catalyst CAT-9.

[0065] Example 10

[0066] 3.0 parts of CoO, 3.0 parts of NiO2, 1.0 parts of CeO2, 3.0 parts of IrO2 and 200 parts of deionized water are prepared into a uniform suspension, and 0.5 parts of PtO2, 0.5 parts of PdO2 and 0.5 parts of magnesium aluminum spinel are added. The liquid is ground into a 20-100 μm slurry by a high-energy ball mill, and then the carrier is coated by deposition complex impregnation using quantitative vacuum coating technology, dried and calcined to make an integral catalyst CAT-10.

[0067] Embodiment 11

[0068] 5.0 parts of CrO2, 5.0 parts of IrO2 and 200 parts of deionized water were prepared into a uniform suspension, and 0.3 parts of PtO2, 0.6 parts of PdO2 and 0.4 parts of magnesium aluminum spinel were added. The liquid was ground into a 20-100 μm slurry by a high-energy ball mill. Then, the carrier was coated by deposition complex impregnation using quantitative vacuum coating technology, and then dried and calcined to make an integral catalyst CAT-11.

[0069] Catalyst effect evaluation:

[0070] Examples 12-22

[0071] In order to evaluate the catalytic effect of the catalyst, in an industrial device, the tail gas of the acrylonitrile absorber was used as the raw material. Under the evaluation conditions shown in Table 1, the tail gas passed through the fixed bed reactor and was detected by gas chromatography. The catalyst activity was measured by the tail gas content. The specific evaluation results are shown in Table 1.

[0072] Table 1 Catalyst evaluation results under evaluation condition 1

[0073]

[0074] As shown in Table 1, the catalyst prepared by the present invention has a non-methane total hydrocarbon content of 16673 ppm, an acrylonitrile content of 40 ppm, a reaction temperature of 400°C, a reaction pressure of 0.01 MPa, and a reaction space velocity of 10000 h -1, under the conditions of mixed gas to air volume ratio (acrylonitrile absorber tail gas to air volume ratio) of 2.5, the non-methane total hydrocarbons after treatment are less than 120ppm, and acrylonitrile is less than 5ppm, indicating that the catalyst of the present invention has good catalytic effect.

[0075] Embodiment 23-33

[0076] In order to evaluate the catalytic effect of the catalyst, in an industrial device, the tail gas of the acrylonitrile absorber was used as the raw material. Under the evaluation conditions shown in Table 2, the tail gas passed through the fixed bed reactor and was detected by gas chromatography. The catalyst activity was measured by the tail gas content. The specific evaluation results are shown in Table 2.

[0077] Table 2 Catalyst evaluation results under evaluation condition 2

[0078]

[0079] As shown in Table 2, the catalyst prepared by the present invention has a non-methane total hydrocarbon content of 16673 ppm, an acrylonitrile content of 40 ppm, a reaction temperature of 550°C, a reaction pressure of 0.01 MPa, and a reaction space velocity of 12000 h -1 , under the conditions of a mixed gas to air volume ratio of 3.0, the total non-methane hydrocarbons after treatment are less than 60 ppm, and acrylonitrile is less than 0.5 ppm, indicating that the catalyst of the present invention has a good catalytic effect.

[0080] Examples 34-44

[0081] In order to evaluate the catalytic effect of the catalyst, in an industrial device, the tail gas of the acrylonitrile absorber was used as the raw material. Under the evaluation conditions shown in Table 3, the tail gas passed through the fixed bed reactor and was detected by gas chromatography. The catalyst activity was measured by the tail gas content. The specific evaluation results are shown in Table 3.

[0082] Table 3 Catalyst evaluation results under evaluation condition 3

[0083]

[0084] As shown in Table 3, the catalyst prepared by the present invention has a non-methane total hydrocarbon content of 16673 ppm, an acrylonitrile content of 40 ppm, a reaction temperature of 610°C, a reaction pressure of 0.012 MPa, and a reaction space velocity of 14000 h -1 , under the conditions of a mixed gas to air volume ratio of 3.3, the total non-methane hydrocarbons after treatment were less than 60 ppm, and acrylonitrile was less than 0.5 ppm, indicating that the catalyst of the present invention has a good catalytic effect.

[0085] Embodiment 45

[0086] In order to evaluate the long-term catalytic effect of the catalyst, the tail gas of the acrylonitrile absorber was used as the raw material in an industrial device. The total non-methane hydrocarbon content was 16673ppm, the acrylonitrile content was 40ppm, the reaction temperature was 550℃, the reaction pressure was 0.01MPa, and the reaction space velocity was 12000h -1 Under the evaluation conditions of 3.0 volume ratio of mixed gas to air, the tail gas passed through the fixed bed reactor and was detected by gas chromatography to investigate the catalytic activity and stability of the catalyst after 1000h of catalysis. The evaluation results are as follows Figure 1 .

[0087] Depend on Figure 1 As shown, the tail gas from the acrylonitrile absorption tower of an industrial device was treated with the catalyst of the present invention for 1000 hours, and the contents of non-methane total hydrocarbons and acrylonitrile in the treated tail gas both met the national emission standards. Therefore, the catalyst of the present invention has good catalytic activity, good stability and long service life.

[0088] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.

Claims

1. A catalyst for treating tail gas from an acrylonitrile absorber, characterized in that: The invention comprises 80-97 parts by weight of a metal skeleton carrier, 0.5-1 parts by weight of an active component, 5-10 parts by weight of an auxiliary agent, and 0.2-0.5 parts by weight of a hydrothermal stable material; Among them, the active component is at least one of platinum oxide and palladium oxide; the auxiliary agent is at least one of titanium oxide, vanadium oxide, chromium oxide, manganese oxide, cobalt oxide, nickel oxide, copper oxide, and rare earth metal oxide; and the hydrothermal stable material is magnesium aluminum spinel.

2. The catalyst for treating tail gas from an acrylonitrile absorber according to claim 1, characterized in that: The metal skeleton carrier is an Al2O3 / Fe2O3 composite carrier.

3. The catalyst for treating tail gas from an acrylonitrile absorber according to claim 1, characterized in that: The active component is at least one of PtO2 and PdO2.

4. The catalyst for treating tail gas from an acrylonitrile absorber according to claim 1, characterized in that: The auxiliary agent is at least one of TiO2, V2O3, CrO2, MnO2, CoO, NiO, CuO, La2O3, CeO2, and IrO2.

5. The catalyst for treating tail gas from an acrylonitrile absorber according to claim 1, characterized in that: The mass fraction of the metal skeleton carrier is 85-97 mass fractions.

6. The method for preparing the catalyst for treating tail gas from an acrylonitrile absorber according to any one of claims 1 to 5, characterized in that: Active components, auxiliary agents, hydrothermal stable materials and water are mixed into a suspension, the suspension is ground, and then the slurry is coated on a metal skeleton carrier, dried, and calcined to obtain a catalyst for tail gas treatment of an acrylonitrile absorption tower.

7. The method for preparing a catalyst for treating tail gas from an acrylonitrile absorber according to claim 6, characterized in that: The step of mixing the active component, the auxiliary agent, the hydrothermal stable material and water into a suspension is: mixing the auxiliary agent and water into a suspension, and then adding the active component and the hydrothermal stable material.

8. The method for preparing a catalyst for treating tail gas from an acrylonitrile absorber according to claim 6, characterized in that: The method for coating the slurry on the metal skeleton carrier is: the metal skeleton carrier is placed in a vacuum environment, and the slurry is coated on the metal skeleton carrier by deposition complexation impregnation at 150-180°C.

9. Use of the catalyst according to any one of claims 1 to 5 in removing non-methane total hydrocarbons and acrylonitrile from tail gas in an acrylonitrile absorber.

10. The use according to claim 9, characterized in that: The reaction conditions for removing non-methane total hydrocarbons and acrylonitrile from the tail gas of the acrylonitrile absorber are: reaction temperature of 240-650°C, reaction pressure of 0.01-0.015MPa, reaction space velocity of 10000-15000h -1 The volume ratio of tail gas from the acrylonitrile absorption tower to air is 2.5-3.5.

Citation Information

Patent Citations

  • Fe molecular sieve catalyst for purifying NOx in acrylonitrile oxidization tail gas and preparation method of Fe molecular sieve catalyst

    CN102513145A

  • Method for removing cyanogens-containing waste gas

    CN102734812A

  • Acrylonitrile device tail-gas treatment technique

    CN101362051A

  • Monolithic catalyst for high-water-content acrylic acid waste gas purification and preparation method of monolithic catalyst

    CN102580734A

  • Honeycomb catalyst for acrylonitrile device waste gas purification and preparation method thereof

    CN102773120A